Occurrence of Herpes Simplex Virus Type 1 in Dental Students: A Cross-Sectional Study: Herpes Simplex Virus Type 1 among Dental Students - Parvaei, Parvin; Osmani, Freshteh; EbrahimianBaghan, Saideh (Journal of Dental School, 2021)
Objectives Herpes viruses are ubiquitous human pathogens that can be found in the oral environment. Dental practitioners have a close relationship with many patients and are at risk of cross-infection. Thus, the herpes simplex virus type 1 (HSV-1) infection as a potential occupational hazard for dental workers is important. This study aimed to measure the level of HSV1 antibody in dental students. Methods This descriptive cross-sectional study was performed on 100 dental students of Birjand University of Medical Sciences during a six-month period. After taking written informed consent, demographic information and history of genital or oral lesions were recorded using a researcher-made questionnaire. Next, peripheral blood samples (5 mL) were taken from the participants, and the level of anti-HSV1 IgG was measured by a pathologist using the respective kit by ELISA. Data were analyzed by SPSS 21. Results About half of the subjects (41%) had contact with HSV1 and were antibody carriers. The prevalence of HSV1 antibody was higher in senior than junior dental students but not significantly (P>0.05). Conclusion The prevalence of HSV1 antibody in dental students evaluated in this study was lower than the level reported in European countries, which may be due to cultural differences; however, further studies are required.